Analisis Rasio Liquiditas dan Rasio Aktivitas Terhadap Kinerja Keuangan Pada Hotel Dalton Makassar - Andi Bintang Balele; Muhtazib Muhtazib; Florida Regula Anus (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study is to analyze the financial performance of Dalton hotel using liquidity ratio and activity ratio. Qualitative data analysis method is used in this study. The finding shows that in the financial statements at the Dalton hotel in the period of 2018-2020, there are fluctuations in the level of liquidity that has been achieved, which in the aspect of liquidity ratio using current ratio calculations, it that can be declared liquid/healthy. Meanwhile, if measured by the aspect of quick ratio, it is also declared liquid/healthy. In terms of cash ratio in 2018 it is declared not liquid/unhealthy, while in 2019 and in 2020 it was declared liquid/healthy. Of these theree aspects, it can be seen that the liquidity rate of Dalton hotel in 2018-2020 is quite good. In the activity ratio of the 2018-2020 period, obtained results where that asset TurnOver can be declared unhealthy/bad. However, in the inventory turnover ratio and receivable turnover ratio, it can be declared halthy/good.